Analisi biostratifrafiche e paleoecologiche delle associazioni a nannofossili calcarei del Paleocene superiore-Eocene inferiore (Site U1409 Newfoundland Ridge, NW Atlantico). - Sorgato, Stefania (2022)
This Master thesis aims to carry out biostratigraphic studies and analyse calcareous nannofossil assemblages from late Paleocene to early Eocene sediments recovered during IODP Expedition 342. In particular, the study material comes from Site 1409 (Hole A, B, C). During the preliminary phase of this investigation some contradictions arose from the relative positions detected for standard biohorizons in different Holes (B and C). We thus decided to spit our record by Holes to prove if these inconsistencies may be due to some mistakes in constructing mcd scale. In fact, this was the case and we eventually decided to propose an alternative depth, the proposed mcd (pmcd), to temporary overcome the problem. A medium to high resolution calcareous nannofossil biostratigraphy is provided that results in precise biostratigraphic classification of the studied interval at Site 1409. This stratigraphic succession expands from late Paleocene to early Eocene, that is from Zone NP9 to Zone NP13 in term of NP calcareous nannofossil zonation (Martini, 1971). A detailed analysis of biostratigraphic results evidenced also the presence of two hiati, the first positioned at the base of the Eocene and the second lying in the upper part of the studied section, between the upper part of Zone NP 12 and the lower part of Zone NP 13. open